Answer:
The answer is 19305
Step-by-step explanation:
Answer:
(- 1, 2 )
Step-by-step explanation:
Given the 2 equations
- 3x - 5y = - 7 → (1)
- 4x + 5y = 14 → (2)
Add the 2 equations term by term to eliminate y , that is
- 7x + 0 = 7
- 7x = 7 ( divide both sides by - 7 )
x = - 1
Substitute x = - 1 into either of the 2 equations and solve for y
Substituting into (1)
- 3(- 1) - 5y = - 7
3 - 5y = - 7 ( subtract 3 from both sides )
- 5y = - 10 ( divide both sides by - 5 )
y = 2
solution is (- 1, 2 )
The answer is (5x - 4y)(2a + b)
10ax + 5bx - 8ay - 4by = 10ax + 5bx - (8ay + 4by) =<span>
= 5x * 2a + 5x * b - (2a * 4y + b * 4y) =
= 5x(2a + b) - 4y(2a + b) =
= (5x - 4y)(2a + b)</span>
Yes, because it can be expressed as the quotient or fraction of two integers you
Answer:
1.30
Step-by-step explanation:
because it's 13 / 10 it means that there is a whole number , 13 - 10 equals 3 oh, so you divide 3 from 100